Pengaruh Word Of Mouth Dan Direct Selling Terhadap Keputusan Pebelian di Toko Snack Umi H. Mustofa Ujungrusi - Khamila, Dian Lilis; Sulistyani, Tri (Major Management, Faculty of Economics and Business, Universitas Pancasakti Tegal, 2021)
The purpose of this study was 1) to determine the effect of word of mouth on purchasing decisions at snack shops of Umi H. Mustofa Ujungrusi, 2) to determine the effect of direct selling on purchasing decisions at snack shops of Umi H. Mustofa Ujungrusi 3) to determine the effect of word of mouth and direct selling together on purchasing decisions at Umi H. Mustofa Ujungrusi's snack shop. The hypothesis in this study is 1) there is the influence of word of mouth on purchasing decisions at Umi H. Mustofa Ujungrusi snack shops, 2). there is an effect of direct selling on purchasing decisions at the snack shop Umi H. Mustofa Ujungrusi, 3) there is an influence of word of mouth and direct selling together on the buying decision at the snack shop Umi H. Mustofa Ujungrusi. The research method used in this research is quantitative descriptive. While the data analysis method used is Spearman rank correlation analysis, multiple correlation analysis, and analysis of the coefficient of determination. The conclusions of this study are 1) there is a strong, positive and significant influence of word of mouth on purchasing decisions at the snack shop Umi H. Mustofa Ujungrusi. This is evidenced from the calculation of the Spearman rank correlation by using SPSS obtained a correlation value of 0.641 with the value of Zitung = 6.377> Ztable = 1.96. 2) there is a strong, positive and significant direct selling effect on purchasing decisions at Umi H. Mustofa Ujungrusi snack shops. This is evidenced from the calculation of the Spearman rank correlation by using SPSS obtained a correlation value of 0.637 with the value of Zitung = 6.696> Ztable = 1.96. 3) there is a strong influence of word of mouth and direct selling together on purchasing decisions at Umi H. Mustofa Ujungrusi snack shops. This is evidenced from the calculation of multiple correlations obtained by a correlation value of 0.733 with a value of Fcount = 56.295> Ftable = 3.09.